Chitosan as an eco-friendly heterogeneous catalyst for Michael type addition reactions. A simple and efficient route to pyridones and phthalazines - Khalil, Khaled; Al-Matar, Hamad; Elnagdi, Mohamed (European Journal of Chemistry, 2010)
Depending on their nature, nitrile activated methylene compounds add readily to β-enaminones in presence of chitosan to yield dienamides, pyridones or pyridine thiones. The dienamides, formed in this manner, can be readily converted to pyridones by stirring in refluxing acetic acid. Reaction of pyridazinones with a mixture containing benzaldehyde, malononitrile and chitosan affords phthalazines that are also produced by reaction of pyridazinone with benzylidene-malononitrile.